An Analysis of Individual Decision Making Behavior Using a Laboratory Setting - Cecil, Earl A.; Lundgren, Earl F. (Academy of Management Journal, 1975)
This article presents an analysis of individual decision making behavior using a laboratory setting. The author states that one's aspiration level is determined by one's history of successes and fa...